2013
DOI: 10.1007/bf03356448
|View full text |Cite
|
Sign up to set email alerts
|

Control methods and monitoring of Agriotes wireworms (Coleoptera: Elateridae)

Abstract: The aim of this paper is to review and interpret relevant work on population monitoring, damage prediction, agronomic strategies, and chemical as well as biological control of Agriotes wireworms in Europe.Wireworm populations and damages are on the rise globally. During the past decade, particularly research on the determination and distribution of Agriotes species has been brought forward. Summarising the recent click beetle surveys throughout Europe, the most widespread destructive species is A. lineatus, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 64 publications
0
45
0
3
Order By: Relevance
“…Wireworms are the rootfeeding larvae of click beetles (Coleoptera: Elateridae), and can cause severe damage to many agricultural crops worldwide (reviewed in Ritter & Richter, 2013;Traugott et al, 2015). Wireworms are the rootfeeding larvae of click beetles (Coleoptera: Elateridae), and can cause severe damage to many agricultural crops worldwide (reviewed in Ritter & Richter, 2013;Traugott et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Wireworms are the rootfeeding larvae of click beetles (Coleoptera: Elateridae), and can cause severe damage to many agricultural crops worldwide (reviewed in Ritter & Richter, 2013;Traugott et al, 2015). Wireworms are the rootfeeding larvae of click beetles (Coleoptera: Elateridae), and can cause severe damage to many agricultural crops worldwide (reviewed in Ritter & Richter, 2013;Traugott et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Boxes and whiskers indicate interquartile ranges and subsequent 1.5-fold interquartile ranges; bold lines represent the median and outlined circles indicate the outliers. Regarding recent investigations on the use of insecticides, Ritter & Richter (2013) came to the conclusion that shortterm control, resulting in a better crop stand, can also be provided by a repulsion of wireworms. Vernon et al (2009) for example found that neonicotinoid seed treatments provided excellent wheat stand protection, but populations of larger and neonate wireworms were not signifcantly reduced in bait traps the following spring.…”
Section: Wireworm Repellencymentioning
confidence: 99%
“…Among all subterranean arthropods, wireworms are one of the most widespread and serious agricultural pests worldwide. The species Agriotes ustulatus appears to be one of the eight most destructive wireworm species in Europe (Furlan et al 2001, Ritter & Richter 2013. This species completes its life cycle within 24 months in north-eastern Italy (Furlan 1998).…”
Section: Introductionmentioning
confidence: 99%
“…They feed on the roots, shoots, tubers and bulbs of many arable and vegetable crops, including maize and other cereals, potatoes and carrots (reviewed in Parker and Howard 2001;Ritter and Richter 2013;Traugott et al 2015). In many of these crops, wireworms are not necessarily the most destructive insects, but are among the most difficult to control, particularly because of their long life cycle and overlapping generations, their polyphagous nature and their adaption to a wide range of agricultural ecosystems, including grassland and arable crops (Furlan 1998;Ritter and Richter 2013;Sonnemann et al 2014;Sufyan et al 2014;Traugott et al 2013Traugott et al , 2015. Wireworms are also able to react quickly to changes in abiotic conditions with vertical migration to depths of 50 cm or more (Fisher et al 1975;Furlan 1998Furlan , 2004Schaerffenberg 1942).…”
Section: Introductionmentioning
confidence: 99%
“…The ban or withdrawal of many of these widely used soil insecticides and the trend to more conservative soil cultivation techniques led to both an increase of wireworm populations and limitation of the options for their control (Barsics et al 2013;Jedlička and Frouz 2007;Ritter and Richter 2013;Vernon et al 2008Vernon et al , 2016. This stimulated research aimed at the development of ecologically acceptable control methods (Ester and Huiting 2007;Kabaluk et al 2005;Kleespies et al 2013;Kölliker et al 2011;Ladurner et al 2009).…”
Section: Introductionmentioning
confidence: 99%